Design Optimisation of Muzzle Brake for Sniper Rifle - Sherif, Mohamed; Abdelsalam, Ossama Ramy; Aboul, Mohamed (Defence Science Journal, 2018)
Muzzle brakes (MBs) have a great effect on reducing the recoil force of weapons during firing. In this paper, optimum MB efficiency, MB force and recoil force for (12,7 x 99 mm) sniper rifle have been studied. The objective is to obtain the optimum area of side openings, inclination angle and number of chambers for the MB in order to increase the MB efficiency and MB force and thereby to decrease their coil force of the weapon. An analytical model for calculating MB efficiency, MB force and weapon recoil force for MBs of two, three and four chambers has been established. This Model is then utilised in combination with design of experiment (DOE) and Response Surface Method (RSM) statistical techniques to develop a smooth response function which can be efficiently used in optimisation formulation. Finally, multi objectives generic algorithm (MOGA) optimisation method has been employed to find the optimum MB design parameters. The optimisation results show that the three or four chambers MBs have no significant effect on reducing the weapon recoil force compared with the two chamber MB for this sniper rifle.